Sustainable Tourism Influencers on Social Media: Trendsetters or Destination Dream-Sellers? - Mandalia, Siska; Hidayat, Taufik (Journal of Indonesian Tourism and Development Studies, 2026)
Social media influencers significantly shape travel trends and traveler behavior in the digital era. This study explores the dual role of social media influencers in the sustainable tourism landscape: whether they function primarily as trendsetters promoting ethical and responsible travel practices or as sellers of destination dreams who commercialize sustainability through aspirational content on platforms such as Instagram, TikTok, and YouTube.Through qualitative content analysis and in-depth interviews with influencers and their followers, the research identifies messaging patterns, perceived authenticity, and the extent to which sustainability is embedded in influencer branding. Research findings show that although influencers often position themselves as sustainability ambassadors, their content prioritizes visual appeal and personal branding over actual environmental or social responsibility. The study concludes that most influencers are closer to the role of destination dream sellers, contributing to the commercialization of sustainable tourism ideas. This study contributes to the discourse on the impact of digital media on sustainable tourism development, offering policymakers, tourism marketers, content creators, and digital media consumers important insights to evaluate influencer-driven messages on sustainable tourism and align influencer marketing with global sustainability goals.